An Unnatural History of Emerging Infections - Barrett, Ron and Armelagos, George J. (Oxford Oxford University Press, 2013)
This book traces the social and environmental determinants of human infectious diseases from the Neolithic to the present day. Despite recent high profile discoveries of new pathogens, the major determinants of these emerging infections are ancient and recurring. These include changing modes of subsistence, shifting populations, environmental disruptions, and social inequalities. The recent labeling of the term ""re-emerging infections"" reflects a re-emergence, not so much of the diseases themselves, but rather a re-emerging awareness in affluent societies of long-standing problems that were previously ignored.
Include Illustrations and Index
Keywords: Communicable diseases -- Emerging infectious diseases--Epidemiology -- Infection